The Effect of Leadership and Work Motivation on Work Loyalty - Hariyanto hariyanto; Nurdin Brasit; Muhammad Yunus Amar (Magister Management, Hasanuddin University, 2020)
This study aims to examine and analyze the influence of leadership and work motivation on work loyalty in all training and development centers of the National Institute of Public Administration Republic of Indonesia located in Makassar, Samarinda, Aceh, and Bandung. Data was collected by a survey method, using a questionnaire instrument made on the Google Form platform and distributed to 290 employees with three job groups, namely structural, functional, and executor. Of the 290 employees, 125 responded. Data is then analyzed using the Structural Equation Model (SEM) with the help of the SPSS AMOS version 2.3 application. The results showed that leadership has a positive and significant effect on job loyalty. The results of the analysis also show that work motivation has a positive and significant effect on job loyalty.